G297(P) Hypertonic saline- an option for treatment of bronchiolitis-a literature review. (25th October 2020) - Kamal, M; Umar, A
Abstract : Bronchiolitis is most common lower respiratory tract infection in children up to 2 years of age. It is most common during the winter months and leading cause of hospitalization of children worldwide. Bronchiolitis is caused by Respiratory syncytial virus (RSV) most of the time but there are other pathogens including adenovirus, rhino/entero virus etc. The current management is minimal handling, oxygen supplementation and NG feeding/intravenous fluids. Many studies and randomized control trials(RCTs) have been done and many are still going on for many years to find other medical solutions for the cure of bronchiolitis. Nebulized hypertonic saline(HS) is one of them which has been under many trials. The aim of this study was to review the current knowledge of HS regarding its efficacy, safety, clinical effects and tolerance in children. We performed a systematic search of the databases PubMed, Pediatrics Pulmonology, European journal of paediatrics, chest physician and Cochrane review for last 5 years. Method: Thirteen clinical studies and Randomized control trials which were done on children treated with hypertonic saline with bronchiolitis hospitalised in an emergency department and general ward were included from year 2014–2019. We included 8 RCT, 1 meta-analysis, 1 Cochrane or 1 decision analysis and 2 Trial sequential analysis and excluded the studies/trials included in Cochrane review 2017 and Meta-analysis 2018. Main outcome of 8 trial out of these 13 trials was 'Length of stay(LOS)' in hospital and 'admission rate' was studied in 1 of these.1 trial used 'fit for discharge' as main outcome in their trial and 2 Trials looked at the cost effectiveness of use of HS in bronchiolitis. Results: The available studies suggest that Hypertonic saline is promising and safe to use in children with bronchiolitis but there is no superiority found when compared with NS or standard care in reducing the length of hospital stay or admission from emergency department. Conclusion: Hypertonic saline is safe to use in children with bronchiolitis but there is no extra benefit of it in reducing the disease severity, admissions rate or length of stay.